PENGARUH SISTEM PERPAJAKAN, DISKRIMINASI, TEKNOLOGI DAN INFORMASI PERPAJAKAN TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK (TAX EVASION) - Charles Silaen; Yessi Mutia Basri; Azhari - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine and analyze the effect of tax system, discrimination, technology and information of taxation against the taxpayer’s perception of ethics of tax evasion. The population in this study is the individual taxpayer listed on KPP Pratama Batam.The sampling technique using purposive sampling method and determination of sample size in this study was calculated by the slovin’s formula obtained by 110 respondents. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 20. The data were analyzed to the test the hypothesis using multiple linear regression analysis approach.The result of the conducted research partial test show that tax system, discrimination, technology and information of taxation affect the tax payer’s perception regarding the ethics of tax evasion with sig. t < 0,05.Keywords: tax system, discrimination, technology and information of taxation, ethical perceptions of taxpayer’s, tax evasion.